Design and experimental research on electromagnetic active suspension with energy-saving perspective. (January 2020) - Wang, Jiajia; Chen, Long; Wang, Ruochen; Meng, Xiangpeng; Shi, Dehua
A hydraulic damper can improve system reliability when it is introduced to an electromagnetic active suspension equipped with a linear motor. In this study, the effect of damping value on the energy consumption of an electromagnetic active suspension system is investigated with an energy-saving perspective. A kinetic model of electromagnetic active suspension is established, and a controller is designed on the basis of a linear quadratic regulator. Three different levels of roads are then chosen as driving conditions, and the corresponding control targets are set. The effects of damping value on energy consumption and dynamic performance of electromagnetic active suspension under different driving conditions are determined. Results show that damping value does not affect dynamic performance at the same weighting factor or the same driving condition in a time domain. Compared with that of an electromagnetic active suspension without a damper in parallel, the energy consumption of the electromagnetic active suspension system initially decreases and subsequently increases as the damping value increases. Therefore, appropriate damping values can significantly reduce energy consumption. In a frequency domain, appropriate damping values can improve driving safety but can slightly deteriorate ride comfort. An integrated electromagnetic actuator is also designed by integrating the linear motor with the hydraulic damper to construct a practical system structure. These parameters are optimized to improve air-gap magnetic field strength. Thus, the initial design of the structure and dimension of the electromagnetic active suspension system is completed. Finally, the prototype is produced and a 1/4 bench test is also conducted to verify the correctness of theoretical research.